The Investigation of Implied Volatility for the FTSE100 Index Options: A Computational Approach - Zhao, Wenjing (2009)
The aim of this study is to present a framework to model the implied volatility of the FTSE 100 index options with real time market data, and to present a prototype software that implements this framework. This dissertation seeks to combine the computational knowledge and option pricing literature, to design and implement a new java application for calculation of implied volatilities and henceforth justify the presence of volatility smile.